Some biological properties of new quinoline-4-carboxylic acid and quinoline-4-carboxamide derivatives - Strigácová, J; Hudecová, D; Varecka, L; Lásiková, A; Végh, D (Folia microbiologica, 2000)
The antimicrobial and morphogenetic effects of fourteen newly synthesized 2-substituted derivatives of quinoline-4-carboxylic acid and quinoline-4-carboxamide were studied using G+ and G- bacteria, yeasts and filamentous fungi. The highest antimicrobial effects were found with substituted quinoline-4-carboxylic acid derivatives. Quinoline-4-carboxamides only weakly influenced the growth of the tested microorganisms. Some derivatives of quinoline-4-carboxylic acid elicited profound changes in the morphology of hyphal tips of Botrytis cinerea, mainly their branching and the release of the cytoplasmic content. Quinoline derivatives, which elicited morphological changes, increased also the permeability of the plasmalemma of plant cells.
Keywords: Anti-Infective Agents; antibakteriální látky; Fungi; Chenopodiaceae; Microbial Sensitivity Tests; Bacteria; houby; Anthocyanins; Quinolines; Botrytis; antiinfekční látky; chinoliny; Anti-Bacterial Agents; anthokyaniny; mikrobiální testy citlivosti